Analisis Manajemen Persediaan Bahan Baku pada PT XYZ di Kota Tangerang (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Inventory plays a crucial role in ensuring the smooth and sustainable operation of a company. Optimal inventory management is necessary to allow operational activities to proceed without disruption. Inefficient inventory management can lead to inventory imbalances, either in the form of overstocking, which increases costs, or stockouts, which hinder the production process. This study aims to analyze and compare the effectiveness of inventory management applied by PT XYZ  using the Economic Order Quantity (EOQ) approach. The research is descriptive in nature, utilizing both quantitative and qualitative data. Descriptive analysis techniques are employed to systematically explain the stages involved, starting with the calculation of EOQ, safety stock, reorder point, maximum inventory, inventory turnover, and total inventory cost. The results of the study indicate that the current inventory management method implemented by the company is not yet efficient. This is evidenced by a comparison of total inventory costs, where the company's existing method results in a cost of IDR 493,713,882, while the EOQ method results in only IDR 417,481,063. The cost difference of IDR 76,232,819 or 15.44% highlights the potential savings achievable through the application of the EOQ method.